Faceted classification: Proposal of fundamental categories to organize thesis and dissertations in a digital library - Pereira, Clayton Martins [UNESP]; Moreira, Walter [UNESP]; Segundo, José Eduardo Santarem (Universidade Federal de Santa Catarina (UFSC), 2021)
Objective: This work presents a proposal of fundamental categories, based on the work of Ranganathan and the Classification Research Group, to be used to construct a faceted navigation interface for a digital library of thesis and dissertations. Methods: A research of applied nature, qualitative approach and exploratory type was carried out, which uses as methods the literature review, the documentary research and a domain analysis combining the bibliometric study and terminological study approaches. Results: Based on the domain analysis, as well as on the consulted theoretical framework, the following fundamental categories were created: Thing, Kind, Process, Operation, Product, By-product, Space and Time. Conclusions: The fundamental categories proposed in this work can contribute significantly to building a faceted search engine for retrieving theses and dissertations in a digital library. Thus, it is expected to eliminate the difficulties currently encountered by users when using a textual search field.
Classificação facetada: Proposta de categorias fundamentais para organizar teses e dissertações em uma biblioteca digital
Keywords: Faceted Classification; Information Retrieval; Knowledge Organization; Meteorology; PMEST formula